Engineering of Src Homology 2 Domain Leading to Sulfotyrosine Recognition With a High Affinity by Integrating a Distinctive Selection Theme and Next-Generation Sequencing - Zhao, Dongping; Li, Chan; Jiang, Haoqiang; Yin, Yuqing; Zhou, Changjing; Huang, Haiming; Qi, Yunkun; Li, Lei (Frontiers in Microbiology, 2022)
Tyrosine sulfation plays a vital role in various biochemical reactions. The sulfated tyrosine (sTyr) has a similar structure to the phosphotyrosine (pTyr), but the number of available sTyr sites is significantly less than that of pTyr sites because mainly of the lack of effective sTyr probes. A few sTyr binders were identified based on the structural similarity by engineering the pTyr binding pocket of an Src Homology 2 (SH2) domain through phage selections against sTyr peptides. Nevertheless, they still interact with pTyr peptides with comparable affinity. This study aims to identify sTyr superbinders using the SH2 domain as the template. We created a distinctive phage selection scheme that separately covered the selections against sTyr and pTyr peptides, followed by next-generation sequencing (NGS). After selections, the phage pools showed strong ELISA signal intensities for both modified peptides, indicating that the variants were evolved with a high affinity for these peptides, which causes the difficulty to identify sTyr-specific binders. By contrast, the NGS data of the selected pools showed significant differences, suggesting the enrichment of sTyr-specific variants during the selections. Accordingly, we obtained the sTyr features based on the NGS data analysis and prioritized a few potential sTyr binders. The variant SH2-4 showed a stronger affinity to sTyr than pTyr and superior to the previous sTyr binders, measured by the Biolayer Interferometry assay. In summary, we described the strategy that integrates the novel selection scheme and NGS data mining to identify sTyr superbinders.